Assessment of drug-induced electrolyte disorders in intensive care units: a multicenter observational study - Ayhan, Yunus Emre; İlerler, Enes Emir and Sosyal, Damla and Bektay, Muhammed Yunus and Karakurt, Sait and Daşkaya, Hayrettin and Karaaslan, Kazım and Sancar, Mesut (Frontiers in Medicine, 2024)
Objective: Electrolyte disorder (ED) is frequently encountered critically ill patients during admission or admission to the intensive care unit (ICU). This study aimed to determine the frequency of ED encountered in ICU patients to evaluate the relationship of ED with drugs. Method: This prospective, multicenter study was conducted in the medical and anesthesiology ICUs of two training and research hospitals and included patients with at least one ED during admission or hospitalization in the ICUs. The relationship between ED and the drug was evaluated by calculating the logistic probabilistic method scale (LPMS) and the expert panel's evaluation. The correlation between EDs and LPMS was determined using Kendal tau. A binary logistic regression model was preferred in the analysis of factors related to ED. Statistical significance was set as p <0.05. Results: A total of 117 patients were included in the study. A total of 165 EDs were detected, including at least one in 88 (75.2%) patients. According to the expert panel, 61 (21.7%) of EDs were drug-related, whereas according to the LPMS, 111 (39.6%) (p<0.001). Mortality (50% vs. 13.7%) and mechanical ventilation rates (52.2% vs. 17.2%) were significantly higher in patients with ED (p<0.001). Patients with ED had 8.352 times higher odds of exhibiting mortality (OR:8.352, %95 CI: 1.598-43.648, p:0.012) and need mechanical ventilation with higher odds of 3.229 (OR:3.229 95% CI:0.815-12.787 p:0.045). Patient who required enteral or parenteral feeding were associated with an increased likelihood of exhibiting ED (respectively OR:30.057, %95 CI:2.265-398.892, p:0.01, OR:5.537, %95 CI:1.406-21.800, p:0.014). Conclusion: EDs are very common in the ICU. Dysnatremia was detected more commonly in other EDs. It has also been found that patients with ED are more often under mechanical ventilation, have more prolonged hospitalizations, and have higher mortality rates than patients without ED. The suitability of LPMS for assessing ED-drug relationships in the ICU context is questioned.